2008
DOI: 10.1016/j.semcancer.2008.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan-mediated CD44 activation of RhoGTPase signaling and cytoskeleton function promotes tumor progression

Abstract: Hyaluronan (HA), a major component of the extracellular matrix (ECM), is enriched in many types of tumors. In cancer patients HA concentrations are usually higher in malignant tumors than in corresponding benign or normal tissues, and in some tumor types the level of HA is predictive of malignancy. HA is often bound to CD44 isoforms which are ubiquitous, abundant, and functionally important cell surface receptors. This article reviews the current evidence for HA/CD44-mediated activation of the ankyrin-based cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
279
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(302 citation statements)
references
References 99 publications
7
279
1
5
Order By: Relevance
“…Additionally, because the cross-talk between PN and HA-CD44 signaling that plays an important role in cushion cell contraction (Fig. 9), HA-CD44 signaling may also target FLNA to activate contractility as has been seen in other cell types (67). We have found similarity both in the expression patterns of PN and FLNA and in the phenotypes of PN and FLNA knock-out mice, each of which have inhibited ECM remodeling of primordial AV valve (10,53).…”
Section: Discussionsupporting
confidence: 61%
“…Additionally, because the cross-talk between PN and HA-CD44 signaling that plays an important role in cushion cell contraction (Fig. 9), HA-CD44 signaling may also target FLNA to activate contractility as has been seen in other cell types (67). We have found similarity both in the expression patterns of PN and FLNA and in the phenotypes of PN and FLNA knock-out mice, each of which have inhibited ECM remodeling of primordial AV valve (10,53).…”
Section: Discussionsupporting
confidence: 61%
“…The binding of various abnormally expressed CD44 molecules to the receptor HA promotes the secretion of MMPs, resulting in ECM degradation, which is closely associated with axillary lymph node metastasis, increased angiogenesis, prognosis and drug resistance (17)(18)(19)(20)(21)(22). It has been shown that HA binds to the CD44 variant that is widely distributed on the surface of the cell membrane during tumor progression, which induces the activation of ankyrin and small G-protein Rho, and the activation of the PI3K-AKT signaling pathway, thereby leading to enhanced tumor cell adhesion, growth, migration and invasion, and resultant tumor progression (23). HA is found to induce the elevation of MMP expression in breast cancer cell lines, which confers enhanced CD44 cleavage and cell migration during the invasion process (17).…”
Section: Discussionmentioning
confidence: 99%
“…HA is a major component of the extracellular matrix of cartilage, which regulates cell proliferation, differentiation, motility, and adhesion directly via receptors such as CD44 [2,3]. In addition to being expressed by many cell types [4,5], CD44 is one of the major HA receptors. HA participates in many functions via the CD44 receptor such as regulation of cartilage metabolism, including osteoclastogenesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%